ChatGPT: is it good for our glaucoma patients? - Wu, Gloria; Lee, David A.; Zhao, Weichen; Wong, Adrial; Sidhu, Sahej (Frontiers in Ophthalmology, 2023)
Purpose Our study investigates ChatGPT and its ability to communicate with glaucoma patients. Methods We inputted eight glaucoma-related questions/topics found on the American Academy of Ophthalmology (AAO)’s website into ChatGPT. We used the Flesch–Kincaid test, Gunning Fog Index, SMOG Index, and Dale–Chall readability formula to evaluate the comprehensibility of its responses for patients. ChatGPT’s answers were compared with those found on the AAO’s website. Results ChatGPT’s responses required reading comprehension of a higher grade level (average = grade 12.5 ± 1.6) than that of the text on the AAO’s website (average = 9.4 grade ± 3.5), (0.0384). For the eight responses, the key ophthalmic terms appeared 34 out of 86 times in the ChatGPT responses vs. 86 out of 86 times in the text on the AAO’s website. The term “eye doctor” appeared once in the ChatGPT text, but the formal term “ophthalmologist” did not appear. The term “ophthalmologist” appears 26 times on the AAO’s website. The word counts of the answers produced by ChatGPT and those on the AAO’s website were similar (p = 0.571), with phrases of a homogenous length. Conclusion ChatGPT trains on the texts, phrases, and algorithms inputted by software engineers. As ophthalmologists, through our websites and journals, we should consider encoding the phrase “see an ophthalmologist”. Our medical assistants should sit with patients during their appointments to ensure that the text is accurate and that they fully comprehend its meaning. ChatGPT is effective for providing general information such as definitions or potential treatment options for glaucoma. However, ChatGPT has a tendency toward repetitive answers and, due to their elevated readability scores, these could be too difficult for a patient to read.